A Post Covid-19 Invasive Renal Mucormycosis with acute renal failure; a case report and review of literature: Post Covid-19 Invasive Renal Mucormycosis with acute renal failure; a case report and review of literature - Narejo, Farzanarasheednarejo; Naseem, Asma; Jafri, Nazar ul IIslam; Shakeel, Shaheera; Akhtar, Syed Fazal (Pakistan Journal of Kidney Diseases, 2024)
Abstract: The worst nightmare of twenty first century has been discoverd, The Coronavirus, has been risen the incidence of mucormycosis during the( COVID-19) pandemic. There are many case reports of rhinoorbito-cerebral and pulmonary mucormycosis. Hypertension, COVID, and mucormycosis are lethal combination associated with high mortality. This is the first case of Covid-19 associated mucormycosis (CAM) in the kidneys from Pakistan. We report the case of a 68-years old woman who presented with fever, abdominal pain and renal failure. Mucormycosis was diagnosed on renal biopsy. She was managed with Amphotericin- B and hemodialysis via tunneled vascular catheter. She refused nephrectomy. The case highlighted CAM can present as localized renal mucormycosis. In this era of Covid pandemic CAM should be in the differential diagnosis